2010
DOI: 10.1063/1.3497273
|View full text |Cite
|
Sign up to set email alerts
|

Dust ion-acoustic solitary and shock waves due to dust charge fluctuation with vortexlike electrons

Abstract: A rigorous theoretical investigation has been made of the dust ion-acoustic (DIA) solitary and shock waves in an unmagnetized dusty plasma (containing vortexlike electrons, mobile ions, and charge fluctuating static dust) by reductive perturbation method. The effects of dust grain charge fluctuation and vortexlike (trapped) electron are found to modify the properties of the DIA solitary and shock waves significantly. The implications of these results for some space and astrophysical dusty plasma systems, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…It follows that flat-trapped electrons introduce some kind of inertia on the propagation of the localized ion-acoustic waves, as shown in Schamel (1972). This effect has also been observed in the study of small amplitude DIA solitary waves with vortex-like electron distribution (Duha et al 2010). Moreover, for both cases of isothermal and flattrapped electrons, the potential well evolves with higher amplitude in the presence of positive dust concentration in comparison to the population of negative dust grains.…”
Section: Arbitray Amplitude Dia-swsmentioning
confidence: 77%
See 2 more Smart Citations
“…It follows that flat-trapped electrons introduce some kind of inertia on the propagation of the localized ion-acoustic waves, as shown in Schamel (1972). This effect has also been observed in the study of small amplitude DIA solitary waves with vortex-like electron distribution (Duha et al 2010). Moreover, for both cases of isothermal and flattrapped electrons, the potential well evolves with higher amplitude in the presence of positive dust concentration in comparison to the population of negative dust grains.…”
Section: Arbitray Amplitude Dia-swsmentioning
confidence: 77%
“…It is well known that such electron distribution modifies the conditions for the existence of nonlinear waves associated with the DIA waves, particularly the DIA solitary and shock waves which are not observed in dusty plasma with isothermal electrons (Schamel 1972(Schamel , 1979Popel et al 2003;Duha et al 2010;Alinejad and Tribeche 2010). In this case, Duha et al (2010) studied small amplitude DIA solitary and shock waves due to dust charge fluctuation with trapped electrons by reductive perturbation method. They showed that the effects of vortex-like/trapped electron distribution modify the properties of the DIA solitary and shock waves.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…El-Wakil et al [11] theoretically investigated higher order contributions to nonlinear DA waves that propagate in a mesospheric dusty plasma with a complete depletion of the background (electrons and ions). Duha et al [7] studied small amplitude DIA solitary and shock waves due to dust charge fluctuation with trapped electrons by reductive perturbation method. They showed that the effects of vortex-like/trapped electron distribution modify the properties of the DIA solitary and shock waves.…”
Section: Introductionmentioning
confidence: 99%
“…Ion acoustic shock waves were studied by Masood et al [7] in an unmagnetized quantum plasma consisting of electrons, positrons, and ions employing the quantum hydrodynamic model where the nonlinear quantum waves are investigated by deriving the Korteweg dust acoustic (DA) solitons was studied in [8] using the Korteweg-de Vries equation, which showed significant discrepancies in the regime of large amplitudes or high soliton speed where the DA solitons were observed experimentally in a dusty plasma [9]. Duha et al [10] made the dust ion-acoustic solitary and shock waves in an unmagnetized dusty plasma containing vortex like electrons, mobile ions, and charge fluctuating static dust. The dust charge fluctuation has an effect on the formation of different types of solitons in unmagnetized dusty plasma [11].…”
Section: Introductionmentioning
confidence: 99%